PENGARUH KOMPENSASI DAN KEPUASAN KERJA DENGAN KOMITMEN DOSEN DI UNIVERSITAS MUHAMMADIYAH CIREBON - Ali Jufri (JMB : Jurnal Manajemen dan Bisnis, 2019)
This study aims to describe and interpret the effect of compensation and job satisfaction on commitment of lecturers at Muhammadiyah University of Cirebon. This research was conducted using a survey method. As the population is merely 257 employees which is more 100 (one hundred) people, the research was a sample study. In addition, the object of this study is 51 (fifty one) employees. There are three conclusions that can be taken: (1) There is a significant and positive influence between compensation to lecturer commitment. The significance of the effect of compensation on lecturer commitment can be seen from the result of the t test which the t count is 8,377> 1,677 then Ho is rejected and Ha is accepted. The determination index is adjusted by 58,9% and the remaining 41,1% is influenced by other unexamined factors. (2) There is a significant and positive influence between job satisfaction and lecturer commitment. The significance of the effect of job satisfaction on lecturer commitment is evidenced by the t test which is calculated at 6.884> 1.677 so Ho is rejected and Ha is accepted. The determination index is adjusted by 49.2% while the remaining 51.8% is influenced by other unexamined factors. (3) There is a significant and positive effect between compensation and job satisfaction on lecturer commitment. This can be proven by the F test which is the calculated F value of 47,624> 3,18 and the determination index value adjusted 66.5% 33.5% is influenced by other unexamined factors.